VARIABILITAS GENETIK HASIL PERSILANGAN TANAMAN TOMAT (Lycopersicumesculentum MILL.) DAN RESIPROKALNYA DI DATARAN RENDAH - Hariyono, Rudi; Zuhry, Elza; ', Deviona (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The objectives of this research to determine the genetic variability from crosses of tomato and resiproc in the lowland. Research carried out at the experimental station in Faculty of Agriculture at the Riau University in June until October 2013. This research used a Completely RandomizedBlock Design,10 treatments and 3 replications, so that there were 30 units of experimental. The treatment consist of 10 genotipes of tomato is IPB T-13 x IPB T–64, IPB T-64 x IPB T–13, IPB T-13 x IPB T-78, IPB T- 78x IPB T-13, IPB T-64 x IPB T-78, IPB T-78 x IPB T-64, IPB T-3 x IPB T-64, IPB T-64 x IPB T-3, IPB T-3 x IPB T-78 and IPB T-78 x IPB T-3. Parameters were observed: the flowering date, harvesting date, plant height, stem diameters, fruit length, fruit diameters, flesh thickness, number of cavities, fruit weight, weight fruit of plants. Genotype IPB T 3 x IPB T 78 has a fastresponse of flowering and harvesting as well as plant height and weight. Genotype IPB T 78 x IPB T 64 has a weight fruit. While genotype IPB T 64 x IPB T 78 has a higher fruit weight per plant (986,1 g). Keyword : Genetic Diversity, Tomatoes, Lowland